Contribution to the knowledge of the oribatid mite genus Setoppia (Acari, Oribatida, Oppiidae), with description of a new species from South Africa - (:unkn) unknown (My University, 2020)
A new species of the genus Setoppia (Oribatida, Oppiidae) is described from soil of Golden Gate Highlands National Park, South Africa. Setoppia paraquattuor n. sp. differs from Setoppia quattuor in having smaller lateral teeth and incision on the tripartite rostrum, shorter notogastral setae h 3 and subequal sized la, lm, lp, and h 2 setae. Summarized generic traits, identification key, distribution worldwide and in South Africa, and habitats of all known species of Setoppia are presented. Keywords oribatid mites; Oppiidae; systematics; morphology; South African fauna; zoogeography; habitat; Afrotropical region Zoobank http://zoobank.org/4D6F6355-D016-450F-9453-B56C661945AF
Keywords: African Research